Lines: A brief history - Ingold, Tim (London Routledge, 2007)
This is the first book to explore the production and significance of lines. As walking, talking, gesticulating creatures, human beings generate lines wherever they go: here, Tim Ingold lays the foundations for an anthropological archaeology of the line. He investigates:speech and song in the cultures of Papua New Guinea, the Navaho and Meso Americapaths, trails and mapsdrawing, writing and calligraphythe modern and postmodern world.Written by a leading expert in the field and including over seventy illustrations, this text offers a radically different approach to anthropological and archaeological studies, taking us on a journey which will change the way we look at the world and how we move within it.